Dihydrotanshinone I protects human chondrocytes and alleviates damage from spontaneous osteoarthritis in a guinea pig model - Yan-Zhuo Zhang; Zhen-Jie Wei; Shu-Nan Yu; Xin-Yu Wang; Ying Wang; Cheng-Ai Wu; Xu Jiang (Scientific Reports, 2023)
Abstract Osteoarthritis (OA) is the most common degenerative joint disease. Currently, no satisfactory pharmacological treatment exists for OA. The potential anti-inflammatory properties of Dihydrotanshinone I (DHT) have been reported, but its effects on OA are unclear. In this study, we assess the impact of DHT on the viability of human chondrocytes in vitro. We then use a guinea pig model to investigate the effects of DHT on knee osteoarthritis progression. Twelve-week-old Dunkin Hartley guinea pigs spontaneously developing OA were intraperitoneally injected with different doses of DHT for eight weeks. Micro-CT analysis was performed on the subchondral bone in the knee, and histological assessment of the knee joint was done using stained sections, the ratio of hyaline to calcified cartilage, and Mankin scores. DHT successfully restored IL-1β-induced decreases in cell viability in human primary chondrocytes. In the guinea pig model, intraperitoneal injections of DHT ameliorated age-induced OA, effectively reduced the expression level of two cartilage metabolism-related genes (ADAMTS4 and MMP13) and decreased the inflammatory biomarker IL-6 in the serum of guinea pigs developing spontaneous osteoarthritis. These findings demonstrate DHT’s protective effects on chondrocytes and suggest that it alleviates cartilage degradation and proteoglycan loss in OA.